Placental weight in first generation migrant mothers in Germany. Do the length of stay, acculturation or migrant status play a role?. (May 2021) - Hinkson, Larry; David, Matthias; Bauman, Charlotte; Borde, Theda; Henrich, Wolfgang; Razum, Oliver; Breckenkamp, Jürgen
Abstract: Introduction: Migration status affects perinatal outcomes. A small placenta is associated with placental dysfunction and poor outcomes. Placental weight and perinatal outcomes are influenced by migrant status, the length of stay and the level of acculturation in the host country. Our aim was to compare placental weight in first generation immigrants to native non-immigrants in a teaching hospital in Berlin. The influence of migrant status, the length of stay and the level of acculturation on placental weight was also ascertained. Methods: At the Charité University Hospital in Berlin Germany between January 2011 and January 2012, 1373 non-migrant and 1243 first generation migrants were included. Data collection was by means of a standardized questionnaire. The level of acculturation was based on the Frankfurter Acculturation Questionnaire (Frankfurter Akkulturationsfragebogen-FRAKK). Demographic parameters such as age, maternal weight, country of origin, parity, anemia, diabetes, hypertension, smoking and neonatal outcomes including neonatal weight, placental weight were measured. Results: We found no difference in mean placenta weight when comparing first generation women with a migration background to women of the native population (608 g vs 597 g, p-value 0.41). There was also no difference in placental weight when assessed by the length of stay and degree of acculturation in the host country. Discussion: While first generation migrant women have increased perinatal complications, there is no influence of migrant status, length of stay and the degree of acculturation on placenta weight. Pregnancy outcomes maybe be more dependent on factors such as the access to adequate maternal care. Highlights: Migrant status affects perinatal outcomes. Small placental weight affects perinatal outcomes. Placental weight is however not affected by migrant status. Length of stay and acculturation have no effect on placental weight in migrants.